Reconhecendo as escolhas de leitura dos jovens : best-seller não é boa leitural - Gonçalles, Mariana Cristine (2016)
The main goal of this Master´s dissertation is to understand the reasons why teenagers choose some kind of ficcional texts to read instead of others. Therefore, taking into consideration the variety of social practices in which adolescents take part and believing in more effective participation of teenagers in some of these practices, two social spheres of reading were determined: the school literature - which consists in books that surround the school environment - and the literature of the cultural industry - which are the best sellers. Thus, the literacy theory was extremely important to the study, as well as the theories about literacy practices and events. Authors such as Brian Street, Angela Kleiman, Roxane Rojo and many others have taken part in our studies. The discussion departed from the belief that teenagers prefer to read cultural industry literature rather than the school literature. This proposition was based on some data related to the production and the selling of best sellers. The corpus of the study was selected after consulting the relashionships website Skoob, in which was searched for highest rates of reading of both school literature and best sellers. For the selection of the school narratives, the corpus was delimited from the novels sent to public schools in Brazil by the National Program of the School Library - Programa Nacional Biblioteca da Escola (PNBE) - 2013 archieve, and for the selection of the cultural industry narratives, the corpus was limited by the most read books concerning the website Skoob. In terms of outcome of this study, the discussions pointed out an existence of some narrative categories which are similar in both social reading spheres, a fact that demonstrates some convergence between the two practices of literacy and also deconstructs the premise that they are two different types of literature and deserve a different appreciation. However, some data related the process of adolecents identification with the readings, urging the belief that the cultural industry literature is more effective than the school literature, justifying the teenager public choices of reading.